Development of Self-Directed Learning-Based Bank and Financial Institution Textbooks to Improve the Quality of Learning - Tjetjep Yusuf Afandi; Bayu Surindra; Elis Irmayanti; Zainal Arifin; Efa Wahyu Prastyaningtyas; Ari Saputri Novita Anggraini (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
One indicator of learning is said to be of quality like the existence of an effective combination of learning media and the methods used in learning. In this case, one of the learning media studied is textbooks combined with self-directed learning based learning methods. Where in the research conducted it is hoped that it will be able to make the quality of learning increase, especially in bank and financial institution courses. The method used in research is research and development (RnD). The stages of textbook development are: preliminary research, problem identification, data collection and textbook preparation, validation by experts, revisions, small-scale trials, follow-up revisions, extensive trials, final revisions, and final textbooks. The results obtained are 1) textbooks are suitable for use in learning from the results of expert validation with a minimum score of 75% to 90%; 2) an increase in student collaboration skills from a score of 77 to 82 and increased to 89; 3) an increase in student activity from a score of 79 to 83 and increased to 93; 4) the learning outcomes of students who scored > 85 also increased from 5 students to 12 students, and increased again to 17 students. Meanwhile, the results of the comparative test with SPSS showed that the Sig.(2-tailed) student collaboration ability was 0.000 <0.05; student activity score Sig.(2-tailed) of 0.000 <0.05; and student learning outcomes with a Sig.(2-tailed) score of 0.000 <0.05, thus indicating a significant difference both before and after the use of textbooks for banks and financial institutions based on self-directed learning.